The Effect of AI Implementation, Logistics Information System Integration, and WMS on Operational Efficiency and Customer Satisfaction in Indonesian Logistics Companies - Rizkha Rida; Margie Subahagia Ningsih (Golden Ratio of Mapping Idea and Literature Format, 2026)
The Indonesian logistics industry is undergoing rapid digital transformation through the adoption of artificial intelligence (AI), Logistics Information System (LIS) integration, and Warehouse Management Systems (WMS). However, empirical studies examining the simultaneous effects of these technologies on operational efficiency and customer satisfaction remain limited. This study investigates the influence of AI implementation, LIS integration, and WMS adoption on operational efficiency and customer satisfaction in Indonesian logistics companies. A quantitative explanatory research design was applied using purposive sampling. Data were collected from 350 respondents, including logistics managers, warehouse supervisors, IT managers, and supply chain coordinators across Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that AI implementation, LIS integration, and WMS adoption have positive and significant effects on operational efficiency. Operational efficiency also significantly improves customer satisfaction. Among the three digital technologies, AI implementation has the strongest standardized effect, followed by LIS integration and WMS adoption. The findings confirm that operational efficiency plays a crucial role in linking digital technology adoption with customer-related outcomes. This study contributes to TAM, RBV, TOE, and Digital Transformation Theory and provides practical insights for improving logistics performance.